Pengaruh Rope Langsung 10, 20, dan 30 Second dengan Interval Training 1: 3 untuk Leg Otot Power dan Agility - Yuyun Dwi Astyorini (Universitas Negeri Semarang, 2016)
This study aimed to analyze: (1) the effects of 10 secondrope jump exercise with interval training 1:3 towards leg muscles power and agilityenhancement, (2) the effects of 20 secondrope jump exercise with interval training 1:3 towards leg muscles power and agilityenhancement, (3) the effects of 30 secondrope jump exercise with interval training 1:3 towards leg muscles power and agilityenhancement, and (4) the difference effect betweenrope 10, 20, and 30 second rope jump to wards leg power muscles and agility enhancement. Type of research used in this research is quasi-experimental methods.Population of this research is male students of Sport Science with the number of sampleare 40man.The data analysis using ANOVA. The data collection process ofagility used the 'TLBZ test and leg muscle power using jumpDF tests during the pre-test and post test. Furthermore, the data were analyzed using SPSS version 21. The research results showed that: (1) The 10 second rope jump exercise with interval training 1:3can increase effect on leg muscles power as big as 28,58% and agility as big as -0,97%, (2) The 20 second rope jump exercise with interval training 1:3 can increase effect on leg muscles power as big as 35,02% and agility -1,42%, (3) 30 second rope jump exercise with interval training 1:3 can increase effect on leg muscles power as big as 40,28% and agility as big as -1,91%, and (4) The 30 second rope jump exercises is the most effective exercise to improve leg muscle power and agility on male sport science students of Surabaya State University.